Cannabis Use Among Aboriginal Youth in the Non-Aboriginal Child Protection Services System - Waechter, Randall; Leung, Eman; Wekerle, Christine; Bennett, Marlyn (First Peoples Child & Family Review, 2011)
The social, cultural and political contexts of vulnerability need to be considered in defining, understanding, and reducing substance abuse among maltreated youth with an Aboriginal background (MacNeil, 2008; Tatz, 1999). Aboriginal cultures tend to incorporate an ideology of collectivism that manifests in shared childrearing responsibilities within aboriginal families and communities (e.g., Dilworth-Anderson & Marshall, 1996). As such, Aboriginal children may identify with multiple and equally important attachment figures, and be more accepting of multiple caring adult guardians who can direct them away from risky behaviour (Christensen & Manson, 2001). We examined the relationship between cannabis use and reported identification with a caseworker among youth-identified Aboriginal and non-Aboriginal adolescents randomly drawn from the active caseload of a large urban non-Aboriginal Child Protection Services (CPS) system. While an Aboriginal-specific child welfare agency exists in this catchment area, youth need to be identified as Aboriginal to be involved in that system and some youth with Aboriginal heritage inevitably end up in non-Aboriginal CPS agencies. There were no significant differences in rates of maltreatment, trauma symptomatology, or overall cannabis use between Aboriginal and non-Aboriginal youth in this study. However, Aboriginal youth who reported a more negative (i.e., low) identification with their caseworker were five times more likely to use cannabis in the past 12 months compared to Aboriginal youth who reported a more positive (i.e., medium-high) identification with their caseworker. These results suggest that having a moderate-to-high positive identification with caseworker may be a protective factor in regard to abstinence from cannabis use among Aboriginal and non-Aboriginal youth in the non-Aboriginal CPS system.